Quantification of scleral changes during dynamic accommodation. (May 2023) - Cabeza-Gil, Iulen; Manns, Fabrice; Calvo, Begoña; Ruggeri, Marco
Abstract: The mechanics of accommodation is a complex process that involves multiple intraocular ocular structures. Recent studies suggest that there is deformation of the sclera during accommodation that may also play a role in accommodation, influencing ciliary muscle contraction and contributing to the accommodative response. However, the type and magnitude of the deformations measured varies significantly across studies. We present high-resolution synchronous OCT measurements of the anterior sclera contour and thickness and lens thickness acquired in real-time during accommodative responses to 4D step stimuli. The lens thickness was used as an assessment of objective accommodation. No changes in nasal and temporal anterior scleral contour and scleral thickness were found during accommodation within the precision of our measurements. Our results demonstrate that there are no significant scleral deformations during accommodation. Highlights: A dynamic OCT study to explore the role of the sclera during accommodation. No changes in anterior scleral contour and thickness due to accommodation were observed with the current methodology. No significant changes in the scleral shape for the temporal and nasal quadrant were observed during accommodation.